Família em transito: Tecendo Redes Sociais - Prado, Angela Elza Fortes de Almeida (2006)
The purpose of this study was to analyze and comprehend the formation and maintenance of the Social Network, from the experience of families that live the internal migrations, either by moving reasons or job transfers from one of the consorts. The study was accomplished through the use of the qualitative resource methodology, with the Case Study approach. The participants were formed by four married couples who attended all the criteria previously established, being invited by the snowball resource. The half-structured interview was adapted as a tool work, as well as the Social Network Map of the participants. The qualitative analysis was used for the comprehension of the phenomena. The knowledge demonstrated with the data analysis revealed that the most important Social Network are those based on family, friendship and work relationships, and also in the common experience of the migration. The migratory process can bring growth, development and countless meaningful transformations to the family relationships, once there is opening and adaptation to the new connections, and a healthy relation with the old ones, demonstrating the importance that the Social Network take on the migration. The migration by itself is a process of Social Network formation that reinforces the social relationships through time and space